The relationship between electrospray ionization behavior and cytotoxic activity of [MI(P)4]+‐type complexes (M = Cu, Ag and Au; P = tertiary phosphine). (29th July 2013) - Tisato, Francesco; Crociani, Laura; Porchia, Marina; Bernardo, Plinio Di; Endrizzi, Francesco; Santini, Carlo; Seraglia, Roberta
<x xml:space="preserve">Abstract</x> RATIONALE To try to find a correlation between the antiproliferative activity of a series of [MI(P)4]+ complexes (M = Cu, Ag and Au; P = tertiary phosphine) and their stability at micromolar concentration under mass spectrometric conditions. METHODS [MI(P)4]+ complexes were investigated by positive ion electrospray ionization mass spectrometry with multiple collisional experiments using an ion trap mass spectrometer. RESULTS The displacement of P from native [MI(P)4]+, previously described for the copper derivative, is common for the triad complexes leading to the formation of [M(P)3]+ and [M(P)2]+ adducts. Further dissociation of [M(P)2]+ depends on the nature of the metal (Cu Ag > Au). More labile [Cu(P)2]+ and [Ag(P)2]+ are more cytotoxic against HCT‐15 human colon carcinoma cells compared to less labile [Au(P)2]+ species. CONCLUSIONS The dissociation of P ligand(s) from the [MI(P)4]+ complexes is the driving force for the triggering of the antiproliferative activity. The more favored is the displacement of P from the [M(P)2]+ active form, the more favored is in turn the possibility for the metal to interact with biological substrates related to cancer proliferation. Copyright © 2013 John Wiley & Sons, Ltd.